Investigating email users behaviour against spam: a proposed theoretical framework - Bujang, Yanti Rosmunie; Hussin, Husnayati (IBIMA, 2012)
Spam is the most common problem faced by email users today when they communicate via the Internet or mobile technology. Despite numerous efforts taken, the battle to contain this problem still goes on. This paper describes a proposed model which focuses on the behavior of email users in avoiding spam while using this popular channel of communication. Based on the Technology Threat Avoidance Theory (TTAT), the model is enhanced by incorporating the ethics perspectives. The enhanced research model is hoped to be able to explain the email users’ behavior in avoiding the spam email as a threat. Several factors have been identified as possibly influencing the behavior of email users, including perceived severity, perceived susceptibility, safeguard effectiveness, safeguard cost, self-efficacy and IT ethics. Although yet to be tested, it is anticipated that a study adopting the proposed model will contribute towards providing the knowledge to the ISP or ESP, decision maker and individual user to handle the spam problem more effectively in addition to the existing approaches. Keywords: spam, TTAT, email user and behavior. __________________________________________________________________________________________________________________